Effects of different doses of organic and inorganic fertilizers on cauliflower yield and soil properties - Devkota, Sabina; Rayamajhi, Kamana; Yadav, Dil Raj; Shrestha, Jiban (Journal of Agriculture and Natural Resources, 2021)
The experiment was conducted in research field of Agriculture Research Station at Belachapi, Dhanusha, Nepal from November, 2017 to February, 2018 to evaluate the effects of different doses of organic and inorganic fertilizers on Cauliflower yield parameters and soil properties. In the experiment, there were ten treatments consisting of different combinations of organic and inorganic fertilizers. The cauliflower variety ‘Snow mystic’ was grown with these treatments laid out in a Randomized Complete Block Design with three replications. The half dose of Organic manure (750 kg/ha) and half dose of farm yard manure (FYM) (20 t/ha) produced the highest curd yield (1019 g) and biomass (2046 g). The highest Nitrogen percent (0.10%), Organic matter percent (1.89%) and Phosphorus content (169.09 mg/kg) were obtained with the application of combined half dose of NPK (105:90:60 kg NPK/ha) and half FYM (20 t FYM/ha). The combined effect of application of Organic manures with inorganic fertilizers (NPK) was found to be better for crop growth and development as well as soil health improvement.